"I'm a bit of a waster": Identifying the enablers of, and barriers to, sustainable food waste practices. (1st December 2020) - Wakefield, Alysia; Axon, Stephen
Abstract: Food waste has become an area of increasing concern in recent years, since unsustainable food waste practices have been associated with a range of adverse environmental, economic and societal impacts. Food waste is a multi-sectoral issue and must be addressed as such, by ensuring policymakers, practitioners, and consumers are equipped with the relevant knowledge and understanding of the importance of sustainable food waste practices. By exploring current attitudes and understanding of this topic amongst consumers, a lack of education about the importance of this issue has been identified as a barrier to carrying out sustainable practices at the household level, along with excess packaging, cultural norms of overconsumption and inappropriate social marketing. In contrast, a number of enablers, including social pressures, access to appropriate facilities and encouragement from media advertisements appear to have been highly influential in infringing on the consciousness of consumers. Investigating these enablers and barriers has allowed a number of potential interventions to be identified, with the intention of addressing this issue using a multifaceted approach and encouraging society to carry out sustainable food waste practices in the future.